Development of Powtoon-Based Learning Videos to Improve Learning Outcomes in Siroh Subjects at Markazur Quraan Baitun Najaah - Sugihati, Yuni; Nurwahidin, Muhammad; Herlinawati, Herlinawati; Firdaus, Rangga (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Powtoon-based learning media has become a popular choice in education to improve learning effectiveness. This scientific article was prepared using the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate and interpret all available research with the topic area of the phenomenon of interest, with specific relevant research questions. The researcher used 10 articles as references in this study. Results Previous studies have shown that the use of Powtoon in learning maths, science and history has yielded positive results. It not only improves comprehension of the material, but also enhances students’ visual appeal, creativity, innovation, learning experience and learning motivation. With attractive animation features, Powtoon creates a dynamic, interactive, and fun learning environment for students. Therefore, the use of Powtoon media can be an effective strategy in improving the quality of learning and student learning outcomes in various subjects.